NEED-GOAL INTEGRATION AND ORGANISATIONAL TYPES; IMPLICATION FOR INDUSTRIAL RELATIONS - Jayeoba, Foluso Ilesanmi (European Scientific Journal, ESJ, 2012)
Organisations are essentially need fulfilling agents. The locus of power in the organisation determines the type as well as the varieties of needs that are met and the types of goals that are set by the organisation. The need-goal integration hypothesis presupposes six organisational types:The traditional management oriented organisation (MOO), Owner oriented organisation (OOO) prevalent among small scale businesses and sole proprietorship, Employee oriented organisation (EOO), Management-Employee oriented organisation (MEOO), Customer oriented organisation (COO), and Ideal oriented organisation (IOO). The implication of an ideal oriented organisation, wide and implicit as it may be, have not been much appraised, much less researched. Focus has narrowed, invariably on fulfillment of only a segment of needs depending on where the pendulum of power swings in the organisation. The forces within the organisation, in most instances, are necessarily centripetal and centrifugal. It takes a balance, albeit delicate and dynamic, amongst the forces in operation to realize the overall potentials - the need fulfilling capacity - of most organisations. The Nigerian organisations as they evolve an ideal oriented approach to management and motivation of the work force need the delicate balance. This theoretical postulation obviously need empirical support which future preoccupations, criticisms and reviews should be focused. Also concepts such as power distance, locus of power will be further explored.